A trispecific antibody targeting EGFR/cMET/VEGF-A demonstrates multiple mechanisms of action to inhibit wild-type and mutant NSCLC animal models - Jin, Ying; Sun, Ping; Chen, Peng; Xu, Yuqiang; Mu, Guangmao; Zha, Zhengxia; Wu, Simin; Fu, Meixia; Jiang, Hao; Huang, Sheng; Zhou, Fulai; Han, Chao; et al. (Frontiers in Oncology, 2025)
IntroductionNon-small cell lung cancer (NSCLC) patients who do not respond to standard of care treatment can have activating mutations in the epidermal growth factor receptor (EGFR) and mesenchymal epithelial transition factor (cMET) signaling pathways, as well as having enhanced levels of vascular endothelial growth factor (VEGF). To combat such resistance mechanisms, TAVO412, was engineered to control aberrant cMET, VEGF-A, and EGFR activities.MethodsIn vitro assays assessed TAVO412’s cell binding, ligand blockade, phosphorylation inhibition, and Fc effector functions. In vivo efficacy was evaluated in NSCLC xenograft models, with subsequent tumor resection for ex vivo quantification of EGFR and cMET levels.ResultsTAVO412 robustly suppressed ligand-induced phosphorylation of EGFR and cMET in NSCLC cell lines. TAVO412 demonstrated more potent antitumor activity than amivantamab and cetuximab in NSCLC xenograft models using cell lines with varying levels of mutant and wild-type EGFR and cMET. In addition, TAVO412 had both EGFR/ cMET receptor degradation and enhanced Fc effector functions for tumor cell cytotoxicity. Moreover, TAVO412 in combination with osimertinib, lazertinib, docetaxel, and radiotherapy, resulted in complete and durable regression of NSCLC xenograft tumors.DiscussionThese findings highlight TAVO412 as a promising therapeutic agent with multiple mechanisms of action and strong potential for synergistic combinations in NSCLC treatment.